Pattern of psychiatric morbidity in children and adolescents attending Psychiatric OPD at a tertiary care hospital: A study from Midwestern Nepal - Khan, TA (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Mental health in child and adolescent is an essential component of overall health. Forty four percent of population in Nepal is under 19 years of age. Majority of lifetime psychiatric illnesses start during child and adolescent stage. Undetected poor mental health has wide range of adverse impact on individual's ability in various domains of achievement. This study is done with the objective to know the pattern of psychiatric morbidity in children and adolescents from a tertiary care hospital. Material and Method: This is a descriptive study comprised of all new cases i.e. 156 participants of child and adolescents visiting to psychiatric outpatients department of Nepalgunj Medical College, Nepalgunj, from January 2017 to June 2017. Socio-demographic data and clinical diagnosis based on International Classification of Disease- 10 diagnostic research criteria were collected and analyzed. Results: Out of 156 subjects studied, 2/3rd were female. The highest (57.06%) number of participants were from age group of 16 year to 18 years. Most common diagnosis was dissociative disorder in 24.35% followed by seizure disorder in 15.38% and mood disorder in 14.75% of participants. Conclusion: Adolescent female were most commonly affected population. Dissociative disorder was the most common psychiatric morbidity followed by seizure disorder and mood disorder. J Psychiatrists’ Association of Nepal Vol .6(1), 2017, p.44-47